STUDI PENINGKATANTINGKAT HUNIAN DI HOTEL ARUSS SEMARANG : PEMASARAN BUSINESS TO BUSINESS, BUSINESS TO CUSTOMER DAN DAYA TARIK KUNJUNGAN WISATAWAN SEBAGAI PREDIKTOR - Achmad Sendek Prawinko; Andhi Supriyadi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
Competition to attract tourists to visit a tourist destination is increasing along with the development of tourism marketing trends in the form of business-to-business and business-to-customer marketing. In this research, a quantitative approach was used with a sample of 103 tourists staying at Hotel Aruss Semarang. Data was collected through questionnaires distributed to respondents. Instrument validity and reliability tests were carried out on data processed using the SPSS program. In addition, a mediation test was carried out to determine whether the visit attractiveness variable had a mediating function, and a hypothesis test was carried out to determine whether the proposed hypothesis was accepted or not. Several conclusions can be made from processing this research data. There is an influence of business-to-business marketing, business-to-customer, and visitor attraction on the occupancy rate of Hotel Aruss Semarang. In a simultaneous test, it was concluded that there was an influence of business-to-business marketing, business-to-customer, and the attraction of tourist visits on the occupancy rate of Hotel Aruss Semarang together.